Variation Of Bamboo and Adhesive Types on Physical And Mechanical Properties Of Particle Board - Gatut Prakosa, Galit; Chanan, Mochamad; Lora, Rinda Laca (International Journal of Science, Technology & Management, 2023)
Bamboo can be used as a material in the manufacture of particleboard. The purpose of this study was to examine the effect of various types of bamboo and their adhesion on the physical and mechanical properties of particleboard. The study used a factorial completely randomized design with three repetitions. Particleboard made using cold pressing made of bamboo betung (Dendrocalamus asper Schult.), bamboo apus (Gigantochloa apus Kurz), bamboo ori (Bambusa arundinacea Retz), and Urea Formaldehyde and Polyvinyl Acetate adhesives. The particle size used was through eight meshes with an adhesive concentration of 20% and a target board density of 1 gram/cm³. Board testing using SNI 03-2105-2006, correlation analysis, and regression to see the relationship between variables. The resulting particleboard has a density between 0.5 – 0.69 gram/cm³, air content between 12.7% - 15.2%, thickness expansion between 2.2% - 17.55%, MOE 1.963 - 4.898 kg/ cm², MOR 4.89 – 9.36 kg/cm². The type of bamboo has no significant effect on density, moisture content, MOE, and MOR of particleboard. The type of adhesive has a significant effect on the density, MOE, and MOR of the particleboard. The interaction between the type of bamboo and the type of adhesive has a significant effect on the thickness development of the particleboard.